Ultrasound-guided intrasacular injection of methotrexate in the management of ectopic pregnancies with embryo. A 12 year experience report in a tertiary hospital. (August 2020) - Alvarez-Sarrado, Leticia; De Bonrostro-Torralba, Carlos; Espiau-Romera, Andrea; Benito-Vielba, Marta; Lasierra-Beamonte, Ana; Campillos-Maza, Jose Manuel
Highlights: Combined MTX therapy is an effective alternative in ectopic pregnancies with embryo. Clinical, ultrasound or analytic characteristics should not entail a contraindication. None of the cervical or abdominal pregnancies required surgery. Where surgery implies a technical difficulty it may decrease morbimortality rates. Abstract: Objective: To evaluate the efficacy and safety of combined-therapy with ultrasound guided intrasacular injection of 50 mg of methotrexate (MTX) and a 50 mg/m 2 dose of systemic MTX in uncomplicated ectopic pregnancies with ultrasonographic evidence of embryonic structures in the gestational sac. Study design: We designed a retrospective study including 60 patients to assess the efficacy of combined MTX treatment and to determine which clinical or ultrasonographic variables could be associated with successful medical treatment. Failed medical treatment was defined when surgery was needed. For statistical analysis, we developed a descriptive analysis and a univariate logistic regression study. Results: Medical approach was effective in 73.3 % of patients. MTX treatment was successful in 32 (68.1 %) out of 47 tubal pregnancies None of the 4 cervical or 2 abdominal pregnancies required surgery. Six (85.7 %) out of 7 cornual pregnancies were successfully treated. No statistically significant differences were found in the success rates according to clinical data, ultrasound or analytic characteristics of women. Conclusion: Combined MTX therapy could be an effective and safe alternative in ectopic pregnancies with embryo in hemodynamically stable women. Clinical, ultrasound or analytic characteristics of patients should not entail a contraindication. In locations where surgery implies a technical difficulty, this option may decrease morbimortality rates frequently associated to a more invasive alternative.